Women’s Intention to Undertake an HIV test: A Concept Analysis - Yeni L. N. Agnes; Sri Haryuni; Kun Ika Nur Rahayu (Journal for Quality in Public Health, 2020)
Background: The intention in the Theory of Planned Behavior is preceded by attitude, perceived control, and subjective norm. This theory had been applied to hundreds of studies from many disciplines. However, when a nurse applies this theory, it requires a detail description related to Muslim wives’ intention to undertake an HIV test. This detailed concept development will help nurses in employing the nursing process accurately to achieve the target of Prevention from Mother to Child Transmission (PMTCT) program. Purpose: The study aims to develop a model of Muslim wives’ intention to undertake an HIV test. Methods: Concept validation of Muslim wives’ intention to undertake an HIV test was traced by using keywords “intention”, “willingness”, “desire”, “HIV tests”, “readiness”, “commitment”, “woman and HIV/AIDS”, “awareness”, in EBSCO, CINAHL, and Proquest. Results: The concept of Muslim wives’ intention was developed from existing theories as deductive origin and literature reviews as an inductive origin. The concept consists of many antecedents that being categorized into two categories includes internal and external factors and six sub-categories as follows internal commitment, knowledge, ethical values, risk perception, demographic factor and subjective norms. Both attribute and consequence key words each have one category. Conclusion: The tentative model can be generalized for other settings or situations. There is no specification that this model just for a specific gender or specific situation.